Effect of Using Roof Clay and Charcoal Ash as a Substitution of Coarse Aggregate and Cement in a Concrete Compressive Strength - Agung Sumarno; Dyah Robbiana Zulfa; Syafwandi; Agyanata Tua Munthe (NAROTAMA UNIVERSITY, Indonesia, 2022)
Infrastructure and technology development in the construction sector are rapidly evolving, particularly in Indonesia. Because practically every construction building is built of concrete, this supports the increased use of natural materials as raw materials for creating concrete to keep up with the world's rapid development. As a result, new technologies are required to limit the use of substitute elements in concrete mixtures while also minimizing environmental damage. The researchers used clay tile waste and charcoal ash as a substitute for coarse aggregate and cement in the concrete mix in this final project. This study uses an experimental approach with a total of 36 samples of cylindrical samples with a size of 10cm x 20cm, a substitution variation of 20%, 25% of total coarse aggregate, and charcoal ash 5% of total cement weight. On days 3, 7, 14, and 28, the test object will be slumped to see how workable it is and how strong it is. According to the findings, the higher the percentage in the concrete mixture, the lower the slump value, and the compressive strength test results. The highest is the 25% GTL substitution variation. At the age of 28, 5% AA equals 27.3 MPa. The results of testing the compressive strength of concrete with the substitution of tile waste reached the quality of K-225.